Connecting scanning tunneling spectroscopy to device performance for polymer:fullerene organic solar cells - Maturová, Klára; Janssen, René A. J.; Kemerink, Martijn (ACS nano, 2010)
Scanning tunneling microscopy and spectroscopy have been used to measure the local photovoltaic performance of prototypical polymer:fullerene (MDMO-PPV:PCBM) bulk heterojunction films with ∼10 nm resolution. Fullerene-rich clusters are found to act as sinks, extracting electrons from a shell layer of a homogeneously mixed polymer:fullerene matrix, surrounding the fullerene cluster. The experimental results were quantitatively modeled with a drift-diffusion model that in first order accounts for the specific morphology. The same model has subsequently been used to calculate performance indicators of macroscopic solar cells as a function of film composition and characteristic size of the phase separation. As such, a first step has been set toward a quantitative correlation between nanoscopic and macroscopic device photovoltaic performance.
Gesehen am 17.12.2019